Study Protocol for a Home-based Obesity Prevention Program in Latino Preschool Children - Taverno Ross, Sharon E. (Transl J Am Coll Sports Med, 2017)
PURPOSE: This paper describes the study design for ANDALE Pittsburgh, a culturally-appropriate, family-based intervention to promote a healthy weight in Latino preschool children. METHODS/DESIGN: The study was organized into two major phases: Phase I: Conduct focus groups with 30 Latino parents of preschool children to inform the development of a culturally-appropriate intervention; Phase II: Test the feasibility and effectiveness of the intervention with 50 families. Participants were recruited from an emerging Latino community through community gatherings, flyers, and word of mouth. Six promotoras (females >18 years, active in community) received 25 hours of training using the intervention curriculum finalized after Phase I. Promotoras delivered the home-based intervention to families over 10, 90-minute weekly sessions that included education, practice, and action (i.e., goal setting). Behavior modification constructs and strategies (e.g., goal setting, problem solving, social support), and building of self-efficacy through healthy recipe preparation and physical activity breaks, were also included. Outcomes (e.g., child BMI) were assessed pre- and post-intervention. Process evaluation assessed fidelity, dose, reach, recruitment, and contextual factors using multiple data sources and mixed methods. DISCUSSION: The ANDALE Pittsburgh study will expand the body of knowledge on interventions to promote a healthy weight in Latino preschool children living in an emerging Latino community. If successful, this approach will be evaluated in a future, larger-scale intervention and provide a potential model to help to address and prevent obesity in this population.